Tactical NAV: Innovation in the US Army. Issue 1 (June 2013) - Adams, Dennis A; Ives, Blake; Junglas, Iris
Increasingly, employees are innovating with their own consumer technologies (such as smartphones and tablets), rather than looking to their companies' IT departments to lead technical innovation. This can give rise to tension between employees and IT departments, and this tension is particularly pronounced in the US military, where long systems development times run headlong into young, technology-savvy soldiers arriving in camp with smartphones, sophisticated applications, and high expectations. In this case study, this phenomenon plays out in the person of a US Army Captain who, using resources obtained via the Internet and while on a tour of duty in Afghanistan, develops and sells an inexpensive iPhone application – Tactical NAV – that provides soldiers with a sophisticated navigation tool.